Evaluation of prescribing indicators in prescriptions of private practitioners in Kolkata, India - Mandal, Pragnadyuti; Mondal, Shirsendu; Das, Anjan; Rahaman, Musfikur; Nandy, Manab; Jana, Swapan (International Journal of Basic & Clinical Pharmacology, 2016)
Background: To assess the prescribing indicators in prescriptions of private practitioners in Kolkata. Methods: In the observational, retrospective, cross-sectional survey, 1830 prescriptions of private practitioners were collected over a 5 years period and assessed using core prescribing indicators as per the World Health Organization “How to investigate drug use in health facilities” tool. Results: Overall the average number of drug per prescription was 3.05±0.91. No drug was prescribed by generic name. Prescriptions with an antibiotics and injections were 30% (549/1830) and 8.12% (149/1830), respectively. Drugs prescribed from essential drug list (EDL) were 29.38% (1640/5582). Conclusion: Poly-pharmacy, lack of generic prescribing, low rate of prescriptions from EDL is the present prescribing scenario of private set-up based practitioners of Kolkata. Regulation and intervention is required to improve the irrational prescribing practices.